SWAKELOLA MANAJEMEN BURUH - Fatwa Zuhaena; Tri Esti Masita; Arinastuti Arinastuti (Media Ekonomi, 2014)
This paper proposed the idea to remove the wage system based on stipulated in Law No. 13 of 2003 on Employment, and build a new system based on the Employment Act with a new revenue-sharing and self-management. The idea is implemented by means of disseminating discourse abolition of the wage system and replace it with a system of profit-sharing and self-managed workers’ sector alliances. And workers alliance solidarity and create strategis for action both mass action and structural measures. Intended structural action is to conduct a judicial review of Law No. 13 of 2003 concerning anything pertaining to wages in the employment relationship, to be blasted in Article 28D (2) of the 1945 Constitution. Then prepare an academic paper about the result and the self-management system in-Law the new Labor Law to be submitted to Parliament and Kemenarkertans. Then the discussion is mengkawal the text has to be approved and implemented. Later sharing system and self-management will be a new system in Employmet Act new. Later there will be no more that workers took to the streets, which is considered to impede the course of the national economy. No more demands for wage increases, minimum wage, working hours, outsouring, freedom of association, and other demands. Because of this new system makes workers obtain kedaulatannya, while industrialist also not left out of the corporate world. With this new system, then sociaty will succesfully obtain justice, well-being and economic independence. Keywords: self-management, profit sharing, wage laborers.